ANALISIS REGISTRASI ULANG PENGUSAHA KENA PAJAK TERHADAP TINGKAT KEPATUHAN PEMENUHAN KEWAJIBAN PAJAK PERTAMBAHAN NILAI (STUDI KASUS KANTOR PELAYANAN PAJAK PRATAMA SAMARINDA) - Huda, Rofiul (EKONOMIA, 2013)
Value Added Tax is a tax on the consumption of goods and services in Indonesia that is imposed on production and distribution. VAT is typically due to transfers of taxable goods or services. Value Added Tax ( VAT ) is one of the sector that affect the state budget. One way to increase the VAT revenue is to supervise the VAT reporting compliance by the taxpayer . But the level of VAT reporting compliance by the taxpayer is not in accordance with what is expected. Therefore in 2012 the Directorate General of Taxation Re-register Taxable Enterpreneur. Formulation of the problem in this study is whether the degree of fulfillment of VAT compliance increased after Taxable Enterpreneur Re-registration in Samarinda Tax Office. The hypothesis of this study is the degree of fulfillment of obligations VAT compliance increased after Taxable Enterpreneur Re-registration.Taxable Enterpreneur Re-registration is the activity to test the subjective and objective responsibility of Taxable Enterpreneur and the result is revoked or not VAT collector. The purpose of this study was to determine whether the level of VAT compliance increased after Taxable Enterpreneur Re-registration in Samarinda Tax Office.In analyzing the problem the authors conducted comparative the rate data of VAT compliance before and after Taxable Enterpreneur Re-registration. Fulfillment of VAT compliance rate is calculated by comparing the amount of the VAT reported to Samarinda Tax Office by the number of Taxable Enterpreneur registered.Based on the analysis it can be concluded that the degree of fulfillment VAT compliance increased after Taxable Enterpreneur Re-registration in Samarinda Tax Office.Â